KORELASI MASALAH SANITASI DI LINGKUNGAN TERHADAP PERISTIWA STUNTING PADA ANAK - Metriana, Metriana (Dian Nuswantoro Semarang, 2024)
The study investigates the link between community environmental sanitation and its impact on children's health and growth, specifically focusing on the correlation with stunting incidents. The study employs a Systematic Review using the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) method. The results of this study are: (1) The use of clean water in environmental sanitation is linked to stunting. Unclean water used by the community for daily needs can lead to diseases like diarrhea and typhoid. If children experience diarrhea at a certain age, it can disrupt their growth, causing stunting. (2) Waste management affects stunting; improper garbage disposal attracts disease vectors. Effective waste management, including proper bin use, is crucial to prevent diseases like diarrhea and safeguard child nutrition, preventing stunting.; and (3) Sanitation in the environment from the aspect of toilet facilities has a correlation with stunting.